Equidad, Género Y Diversidad En Educación - DomÃnguez, Yolanda Márquez; Gutiérrez-Barroso, Josué; Gómez-Galdona, Nayra (European Scientific Journal, ESJ, 2017)
Education has a significant role to play in the lives of everyone. Schools are still one of the ways of achieving valuable goals in education, both socially and individually. Education has an impact on our health, political participation, equal opportunities, environment, economy, culture, citizenship, human rights, and on the equitable distribution of social benefits (PÃ©rez-Jorge, MÃ¡rquez-DomÃnguez, GÃ³mez-Galdona, De la Rosa-Hormiga & Marrero-Morales, 2016). Education offers people the opportunity to make decision regarding their own lives; to use their abilities; to take care of themselves as well as other people; to maintain our high expectations and interests; and to make social and political participation possible. In that sense, education is a way to make us free and in living a fulfilled life. In this essay on â€œEquity, Gender and Diversity in Educationâ€, it will be exposed (starting from the initial idea on the importance of education) that nowadays, schools (education), despite all the technological advancement and educational reforms, has little to do with an ideal model of diversity and gender directed towards equal opportunities in education (Criado, 2004). In this study, we will try to analyze the treatment that is being carried out by public policies about gender equality and diversity. Also, we will make significant contributions, if possible, to the debate and reflect on the achievement of quality and inclusive education. This contribution is one that is able to respond to the educational need for diversity in education.